PENGARUH MEDIA AUGMENTED REALITY TERHADAP HASIL BELAJAR SISWA PADA PEMBELAJARAN PAI KELAS VIII DI SMP NEGERI 16 BANDAR LAMPUNG - Nurul Rahmatul Azkiya azkiya; Baharudin Baharudin; Dedy Irawan Dedy Irawan (Ilmuna: Jurnal Studi Pendidikan Agama Islam, 2026)
The study was conducted to determine whether there is an effect of the use of Augmented Reality learning media on student learning outcomes in PAI learning for class VIII at SMP 16 Bandar Lampung, especially on the material on the procedures for eclipse prayers, istiqa' prayers, and funeral prayers. In this study, the researcher used a quantitative approach in the form of a quasi-experimental design. The research instrument was in the form of a test assessment to assess cognitive learning outcomes and also a non-test assessment to assess psychomotor learning outcomes. The data analysis of this study used prerequisite tests, namely normality tests and homogeneity tests, then conducted a hypothesis test using a non-parametric test, namely the Mann-Whitney U Test. The novelty of this study lies in the study of the effect of Augmented Reality media on student learning outcomes in PAI learning which includes two aspects at once, namely cognitive and psychomotor aspects, which are still rarely studied simultaneously. The results of the study showed that in the cognitive domain, a significance value of 0.492> 0.05 was obtained, so there was no significant difference between the experimental class and the control class. Meanwhile, in the psychomotor domain, a significance value of 0.000 < 0.05 was obtained, indicating significant variation between the two groups. The results of the study indicate that Augmented Reality media is more effective in improving learning outcomes in the psychomotor aspect compared to the cognitive domain.